2012
DOI: 10.1093/ejo/cjs053
|View full text |Cite
|
Sign up to set email alerts
|

Matrix metalloproteinases -1, -2, -3, -7, -8, -12, and -13 in gingival crevicular fluid during orthodontic tooth movement: a longitudinal randomized split-mouth study

Abstract: This randomized split-mouth study aimed to examine the levels of matrix metalloproteinases (MMPs) -1, -2, -3, -7, -8, -12, and -13 in the gingival crevicular fluid (GCF) at different time points during orthodontic tooth movement. A total of 16 healthy orthodontic subjects (7 females, 9 males; mean age, 17.7 years) who needed their first upper premolars extracted were enrolled. One randomly chosen maxillary canine was subjected to a distalizing force and was considered to be the test side. The contralateral can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 22 publications
0
11
1
Order By: Relevance
“… 59 MMP-9 is responsible for cleavage of denatured collagen, i.e gelatin; 60 MMP-13 dissolves native fibrillar collagen; MMP-1 is an interstitial collagenase hydrolyzing mainly type III collagen, 61 and MMP-3 is responsible for activation of MMPs 8 and 9. 62 Hence peaks of MMP8 and MMP9/NGAL ratio at 14d 17 and 72hr, 13 respectively, occur subsequent to peak of MMP-3 in 1hr/24hr. 17 , 20 In vitro studies also support rise in MMPs in orthodontic forces, specifically MMP-1,2 mRNA and protein production in human gingival and pdl fibroblasts 63 , 64 and MMP-1,2, 9 in gingival tissue of dogs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 59 MMP-9 is responsible for cleavage of denatured collagen, i.e gelatin; 60 MMP-13 dissolves native fibrillar collagen; MMP-1 is an interstitial collagenase hydrolyzing mainly type III collagen, 61 and MMP-3 is responsible for activation of MMPs 8 and 9. 62 Hence peaks of MMP8 and MMP9/NGAL ratio at 14d 17 and 72hr, 13 respectively, occur subsequent to peak of MMP-3 in 1hr/24hr. 17 , 20 In vitro studies also support rise in MMPs in orthodontic forces, specifically MMP-1,2 mRNA and protein production in human gingival and pdl fibroblasts 63 , 64 and MMP-1,2, 9 in gingival tissue of dogs.…”
Section: Discussionmentioning
confidence: 99%
“… 62 Hence peaks of MMP8 and MMP9/NGAL ratio at 14d 17 and 72hr, 13 respectively, occur subsequent to peak of MMP-3 in 1hr/24hr. 17 , 20 In vitro studies also support rise in MMPs in orthodontic forces, specifically MMP-1,2 mRNA and protein production in human gingival and pdl fibroblasts 63 , 64 and MMP-1,2, 9 in gingival tissue of dogs. 60 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…72,[79][80][81][82] The GCF level of MMPs and their inhibitors has been generally shown to peak at an average of 1 to 2 days after the application of the stimulus and return to baseline values after approximately 1 week. [83][84][85] The role of RANKL and its inhibitor OPG in inducing alveolar bone remodeling during orthodontic tooth movement has been demonstrated. 39,40,86 Based on the observations of various studies, it can be concluded that the analysis of GCF mediators reflects the biological activity that occurs in the periodontium during orthodontic tooth movement.…”
mentioning
confidence: 99%
“…Orthodontic loading is an intentional mechanical stimulation using orthodontic devices to increase bone turnover around teeth to achieve the desired positions for improved function and esthetics. An early increase in the signaling of chemokines or cytokines, including Prostaglandin E2 (PGE-2), cyclic adenosine monophosphate (cAMP), tumor necrotic factor-α (TNF-α), interleukin-1 β (IL-1 β) occurs during orthodontic tooth movement (OTM) 1 , 2 , 3 , 4 and the downstream effectors, matrix metalloproteinases (MMPs), exhibit increased expression upon mechanical loading on either the tension or pressure side, 5 , 6 , 7 indicating that MMPs play a critical role in increasing extracellular matrix turnover, a fundamental part of OTM.…”
Section: Introductionmentioning
confidence: 99%